Understanding Public Perception of and Participation in Non-Revenue Water Management in Malaysia to Support Urban Water Policy - Chee, Hui Lai; Ngai, Weng Chan; Roy, Ranjan (MDPI, 2017)
In contextualising the serious water loss, inefficient resource utilization, and ineffective water utility management in Malaysia, the objective of this study is to understand the public’s perception of non-revenue water (NRW) management in order to provide policy inputs, and to determine ways to improve public participation in NRW reduction. Findings reveal that there is currently only meagre public participation in NRW management in Malaysia, with a majority of the respondents demonstrating a lack of knowledge and awareness on NRW; over-dependence on water utility and government agencies in reducing NRW rates; and failure to submit a report when a leaking pipe is noticed. Educating the public on the importance of reducing NRW and promoting public interests and concerns around water tariffs, is essential to improve NRWreductions in Malaysia. Community-led strategies to better engage the public in addressing NRW-related issues have to be enhanced. To this end, concrete policy implications derived from the findings of the study are outlined.